2016
DOI: 10.1007/s12975-016-0495-1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Axonal Damage and Repair after Central Nervous System Injury

Abstract: Central nervous system (CNS) injury initiates spatial and temporal neurodegeneration. Under pathologic conditions, damaged glial cells cannot supply sufficient metabolites to neurons, leading to energy deficiency for neuronal axons. The widespread disruption of cellular membranes causes disturbed intracellular signaling via dysregulated ionic gradients in neurons. Although several deleterious cascades are activated during the acute phase of CNS injury, some compensatory responses may tend to promote axonal rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 61 publications
0
42
0
Order By: Relevance
“…Several clinical studies reported that fiber tract integrity was significantly related to motor impairment in patients with stroke [5,6]. Moreover, a significant body of evidence supports the importance of axonal reorganization in recovery after stroke [7][8][9][10][11]. The interplay between growth factors and microvascular cells prompts axonal sprouting and facilitates functional recovery [12].…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical studies reported that fiber tract integrity was significantly related to motor impairment in patients with stroke [5,6]. Moreover, a significant body of evidence supports the importance of axonal reorganization in recovery after stroke [7][8][9][10][11]. The interplay between growth factors and microvascular cells prompts axonal sprouting and facilitates functional recovery [12].…”
Section: Introductionmentioning
confidence: 99%
“…As a glycan epitope, HNK-1 is always associated with sulfoglucuronylglycolipids and glycoproteins. It has been confirmed that HNK-1 is widely found in the CNS and PNS and participates in various neural functions, including myelination, neurite outgrowth, and synaptic regeneration after nerve injury [145]. Absence of HNK-1 results in brain dysfunction such as defective synaptic plasticity and spatial learning [146,147].…”
Section: Human Natural Killer-1 (Hnk-1) Mimicking Natural Compoundmentioning
confidence: 98%
“…The ability of a CNS neuron to regenerate following injury may be dependent on both its intrinsic growth capacity and the extracellular environment enriched by the cell-cell network [5][6][7]44]. In this section, the intrinsic mechanisms of neuronal axon regeneration will be discussed.…”
Section: Effects Of Co On Neuronal Intrinsic Mechanismsmentioning
confidence: 99%